So Much to Read, So Little Time: How Do We Read, and Can Speed Reading Help?. (May 2016) - Rayner, Keith; Schotter, Elizabeth R.; Masson, Michael E. J.; Potter, Mary C.; Treiman, Rebecca
The prospect of speed reading—reading at an increased speed without any loss of comprehension—has undeniable appeal. Speed reading has been an intriguing concept for decades, at least since Evelyn Wood introduced her Reading Dynamics training program in 1959. It has recently increased in popularity, with speed-reading apps and technologies being introduced for smartphones and digital devices. The current article reviews what the scientific community knows about the reading process—a great deal—and discusses the implications of the research findings for potential students of speed-reading training programs or purchasers of speed-reading apps. The research shows that there is a trade-off between speed and accuracy. It is unlikely that readers will be able to double or triple their reading speeds (e.g., from around 250 to 500–750 words per minute) while still being able to understand the text as well as if they read at normal speed. If a thorough understanding of the text is not the reader's goal, then speed reading or skimming the text will allow the reader to get through it faster with moderate comprehension. The way to maintain high comprehension and get through text faster is to practice reading and to become a more skilled language user (e.g., through increased vocabulary). This is because language skill is at the heart of reading speed.